USING OF N-DIMENSIONAL EUCLIDEAN DISTANCE TO DETERMINE LOCATION WITH LACK OF HOSPITAL WITH HEALTH SOCIAL SECURITY AGENCY SERVICE - Alif, Satrio Muhammad; Lestari, Mardiana Tri (Universitas Sebelas Maret (UNS), 2022)
Health Social Security Agency or Badan Penyelenggara Jaminan Sosial Kesehatan (BPJSK) is a health to make people pays inexpensive price to get medical treatment. One of the shortcomings of BPJSK is regency of BPJSK card owner must be identical with the regency of target hospital. Lampung Province has varying location and uneven distribution of hospitals especially in regencies. This study aims to determine location with lack of hospital with BPJSK by using of n-dimensional Euclidean distance. The three-dimensional coordinate of 2098 sample points (SP) and 77 hospitals are the quantitative parameter used to calculate the distance. Every hospital and SP are assigned an identity number depending on the regency of each hospital and SP. Each SP pairs with its closest hospital. The SP with different identity is grouped. 32.1% of area of Lampung Province is the location with lack of hospital with BPJSK. The most prioritized regencies is Pringsewu Regency based on the distance and the population. Further research about spatial analyzing the exact location to build hospital with BPJSK service should be conducted.